2022
DOI: 10.1007/s11357-022-00547-x
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of disability-free survival in healthy older people

Abstract: Prolonging survival in good health is a fundamental societal goal. However, the leading determinants of disability-free survival in healthy older people have not been well established. Data from ASPREE, a bi-national placebo-controlled trial of aspirin with 4.7 years median follow-up, was analysed. At enrolment, participants were healthy and without prior cardiovascular events, dementia or persistent physical disability. Disability-free survival outcome was defined as absence of dementia, persistent disability… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 15 publications
(3 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…Another systematic review also found an association between walking speed and the probability of disability [ 32 ]. A recently developed prediction model demonstrated that age, walking speed, and cognitive function were the strongest predictors of disability-free survival in healthy older people [ 33 ]. We only found two studies, both longitudinal, carried out in the Netherlands aimed at predicting disability assessed with the GARS by frailty items [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Another systematic review also found an association between walking speed and the probability of disability [ 32 ]. A recently developed prediction model demonstrated that age, walking speed, and cognitive function were the strongest predictors of disability-free survival in healthy older people [ 33 ]. We only found two studies, both longitudinal, carried out in the Netherlands aimed at predicting disability assessed with the GARS by frailty items [ 34 , 35 ].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, older adults individuals who achieved the recommended MVPA level of 150 min per week exhibited superior cognitive function relative to those who failed to meet this standard; the latter group was 1.63 times more likely to experience cognitive decline ( 10 ). Furthermore, in both genders of the older adults, higher age, lower cognitive function, lower gait speed, and lower grip strength were predictors of difficulty living with disability ( 11 ). Over a 10-year follow-up of 1,096 participants with a mean age of 69.4 ± 5.8 years, the group with the lowest grip strength had a significantly greater decline in cognitive function compared to the group with the highest grip strength (estimate = 0.06, p = 0.039), indicating that low grip strength can predict 10 years of cognitive decline ( 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…However, with many societies experiencing rapid aging of their populations, another social and economic imperative is to maintain an individual’s independence as long as possible, thereby reducing the need for institutional care. Disability-free survival, defined as survival free of severe physical disability or dementia has been proposed as a surrogate measure of independence, of particular relevance to studies of older people ( 10 ). To date, there is little information available about the impact of occupational factors on this important measure of population health.…”
Section: Introductionmentioning
confidence: 99%